(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article discusses how dance and somatic education can challenge the ideal of the "superbody" and proposes vulnerable corporealities as strategy to confront the Capitalocene. Starting from references such as Haraway, Krenak, and Tsing, from practices inspired by Klauss Vianna and Martha Graham and from the coexistence with tentacular beings, such as earthworms, the research culminated in the creation of the body practice Movimentos Tentaculares and the stage work 2415. These experiences explored vulnerability as a potency and questioned anthropocentric hierarchies, mobilizing the audience to reflect on multispecies futures.